2021
DOI: 10.3389/fcell.2021.761134
|View full text |Cite
|
Sign up to set email alerts
|

Identification of m6A Regulator-Associated Methylation Modification Clusters and Immune Profiles in Melanoma

Abstract: RNA N6-methyladenosine (m6A) modification in tumorigenesis and progression has been highlighted and discovered in recent years. However, the molecular and clinical implications of m6A modification in melanoma tumor microenvironment (TME) and immune infiltration remain largely unknown. Here, we utilized consensus molecular clustering with nonnegative matrix factorization based on the melanoma transcriptomic profiles of 23 m6A regulators to determine the m6A modification clusters and m6A-related gene signature. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 66 publications
(70 reference statements)
0
4
0
Order By: Relevance
“…Melanoma tumorigenesis and progression has been linked to dysregulation of epigenetic mechanisms, such as chromatin remodeling complexes (INO80 [ 59 , 60 ], ISWI [ 61 , 62 ], and SWI/SNF [ 63 , 64 , 65 ]); histone post-translational modifications (PTMs) by histone acetyltransferases (HATs) [ 66 ], deacetylases (HDACs) [ 67 ], methyltransferases (HMTs) [ 68 ], and demethylases (HDMs) [ 69 ]; histone variants [ 70 , 71 , 72 ]; DNA [ 73 , 74 , 75 ] and RNA [ 76 , 77 , 78 ] methylation; plus non-coding [ 79 , 80 , 81 , 82 ], micro- [ 83 , 84 , 85 ], and circular [ 86 , 87 , 88 ] RNA. Unsurprisingly, epigenetic changes are also linked to immune [ 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 ] and targeted [ 98 , 99 , 100 , 101 , 102 , 103 ] therapy resistance. Therapy resistance develops rapidly and is unlikely to be driven by de novo mutations [ 17 , 104 ].…”
Section: Role Of the Epigenome In Therapeutic Resistancementioning
confidence: 99%
“…Melanoma tumorigenesis and progression has been linked to dysregulation of epigenetic mechanisms, such as chromatin remodeling complexes (INO80 [ 59 , 60 ], ISWI [ 61 , 62 ], and SWI/SNF [ 63 , 64 , 65 ]); histone post-translational modifications (PTMs) by histone acetyltransferases (HATs) [ 66 ], deacetylases (HDACs) [ 67 ], methyltransferases (HMTs) [ 68 ], and demethylases (HDMs) [ 69 ]; histone variants [ 70 , 71 , 72 ]; DNA [ 73 , 74 , 75 ] and RNA [ 76 , 77 , 78 ] methylation; plus non-coding [ 79 , 80 , 81 , 82 ], micro- [ 83 , 84 , 85 ], and circular [ 86 , 87 , 88 ] RNA. Unsurprisingly, epigenetic changes are also linked to immune [ 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 ] and targeted [ 98 , 99 , 100 , 101 , 102 , 103 ] therapy resistance. Therapy resistance develops rapidly and is unlikely to be driven by de novo mutations [ 17 , 104 ].…”
Section: Role Of the Epigenome In Therapeutic Resistancementioning
confidence: 99%
“…To identify m6A modification clusters and m 6 A-related gene signatures, consensus molecular clustering with non-negative matrix factorization based on the melanoma transcriptomic profiles of 23 m6A regulators was applied to more than 1000 melanoma samples and showed that m6A modifications were involved in melanoma TME immunoregulation and facilitated tumour immunogenicity development. 70,71 Significant differences in tumour-associated immune infiltration between two m6A clusters were identified by analysing the m6A cluster and immune infiltration phenotypes in public datasets. 72 Anti-tumour immune responses were exerted by innate and adaptive immune cells, such as macrophages, polymorphonuclear neutrophils, natural killer cells and dendritic cells (DCs) in the TME.…”
Section: M6a and Melanomamentioning
confidence: 99%
“…m6A modification roles have been identified in the melanoma tumour microenvironment (TME), with immune infiltration roles gradually uncovered. To identify m6A modification clusters and m 6 A‐related gene signatures, consensus molecular clustering with non‐negative matrix factorization based on the melanoma transcriptomic profiles of 23 m6A regulators was applied to more than 1000 melanoma samples and showed that m6A modifications were involved in melanoma TME immunoregulation and facilitated tumour immunogenicity development 70,71 . Significant differences in tumour‐associated immune infiltration between two m6A clusters were identified by analysing the m6A cluster and immune infiltration phenotypes in public datasets 72 .…”
Section: M6a and Skin Cancermentioning
confidence: 99%
“…This means that immunotherapy may preferentially benefit patients with substantial CD8+ T infiltration in the TME. Therefore, predicting response to ICIs based on the characteristics of TME is a critical step to improve response to existing ICIs therapy ( 7 ).…”
Section: Introductionmentioning
confidence: 99%